Complications associated with surgical removal of impacted mandibular third molar - Tripathi, Shashank; Mishra, Ravish; Yadav, Deepak; Kandel, Laxmi; Singh, Harender (Journal of Chitwan Medical College, 2026)
Introduction: Extraction of impacted third mandibular 3rd molar by surgery is one of the commonly performed procedures by the oral and maxillofacial surgeon. This study assessed the demographic data of patients and analysed the associated complications with the mandibular third molar surgical extraction. Method: This prospective observational study at Universal College of Medical Sciences, Nepal, between 24 Jan 2022 and 19 Dec 2024, included 520 patients aged 18–45 years who required surgical removal of mandibular third molars. Postoperative pain, swelling, trismus, infection, nerve injury, alveolar osteitis, and bleeding were assessed at postoperative days (POD) 3, 7, and 14, and at 3 months. Ethical approval was obtained. Descriptive statistics were used to summarize baseline characteristics. Chi-square and Fisher’s exact tests were applied to assess associations between variables. Binary logistic regression analysis was performed to identify predictors of postoperative complications at POD 7. A p-value <0.05 was considered statistically significant. Result: Majority of patients were aged 26–35 years, 239(46.2%). Almost equal gender distribution was seen. Postoperative complications were more frequent in patients aged >35 years, with higher rates of pain (59.0%), swelling (41.0%), and trismus (24.0%) compared with those ≤25 years (p=0.03). Smokers (n=136) showed significantly higher rates of pain (57.4%), swelling (43.4%), and trismus (26.5%) than non-smokers (p=0.01). Complications varied by impaction type and longer duration; >60 minutes was strongly associated with increased complications. Conclusion: Our findings confirm that post-operative complications after the removal of impacted third molars are common but short-lived.